1986
DOI: 10.1113/jphysiol.1986.sp016115
|View full text |Cite
|
Sign up to set email alerts
|

Efferent discharges recorded from single skeletomotor and fusimotor fibres in man.

Abstract: SUMMARY1. Experiments were performed on awake human subjects in which single nerve fibre activity was recorded in the lateral peroneal nerve using tungsten micro-electrodes as described by Hagbarth & Vallbo (1967, 1968a).2. The discharge of twelve single efferent fibres innervating the tibialis anterior muscle (t.a.) or the extensor digitorum longus muscle (e.d.l.) was recorded. On the basis of their functional activity, six fibres were identified as skeletomotor and six as fusimotor fibres.3. Skeletomotor fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 63 publications
2
49
2
Order By: Relevance
“…They were sampled at 10 kHz. Contrary to our previous studies (Ribot et al 1986;Ribot-Ciscar et al 2000), the use of a highly sensitive photocell was not possible in the present one. Indeed, the movement amplitudes were incompatible with the very short distance (5 mm) between muscle tendon and transducer necessary for it to be sensitive to tiny displacements of the muscle tendon.…”
Section: Data Recordingscontrasting
confidence: 53%
“…They were sampled at 10 kHz. Contrary to our previous studies (Ribot et al 1986;Ribot-Ciscar et al 2000), the use of a highly sensitive photocell was not possible in the present one. Indeed, the movement amplitudes were incompatible with the very short distance (5 mm) between muscle tendon and transducer necessary for it to be sensitive to tiny displacements of the muscle tendon.…”
Section: Data Recordingscontrasting
confidence: 53%
“…On the other hand, from observations in the high decerebrate locomoting cat it was deduced that static fusimotor firing was maintained at a tonic level while dynamic discharge was strongly modulated (Murphy, Stein & Taylor, 1984). Human microneurography has indicated changes in fusimotor activity during limb movements, but these changes have not been specified as static or dynamic (Vallbo, 1985;Ribot, Roll & Vedel, 1986). Clearly, there is a need for more data to be gathered on spindle behaviour in a variety of conditions and this paper presents results from some new experiments on jawclosing muscle spindles in the lightly anaesthetized cat.…”
mentioning
confidence: 99%
“…We found that target-guided contractions produced more 7-9 Hz coherence among MUs than self-guided contractions, which is consistent with the predicted effects of an increase in the magnitude or gain of afferent feedback. Such a change in afferent feedback and/or fusimotor activity might have stemmed from changes in the cognitive aspects of the task (Hospod et al 2007;Ribot et al 1986;Ribot-Ciscar et al 2000, changes in sympathetic drive (Abila et al 1985), or the change in force dynamics associated with error correction (Marsden et al 1970). Our results suggest that the absence/ presence of a target underlies changes in tremor previously associated with the general absence/presence of visual feedback.…”
Section: Discussionmentioning
confidence: 66%